Analysis of Greenhouse Gas Emission From Aircrafts and Ground Service Equipment at Tribhuvan International Airport of Nepal - Acharya, Ramesh; Bhattarai, Nawaraj (Journal of Advanced College of Engineering and Management, 2021)
This paper highlights the trend of carbon dioxide emission and its reduction measure at Tribhuvan International Airport, which is the only international airport of Nepal. The landing and take-off (LTO) cycle of three-year (2016 to 2018) data were gathered from Civil Aviation Authority of Nepal (CAAN) for all types of aircrafts and fuel consumption data of each ground service equipment (GSE) were collected from Nepal Airlines Corporation (NAC). With the help of LTO emission factors published by different institutions and collected data, the emission was calculated and overall (international, domestic, helicopters and GSE) CO₂ emission in the year 2016, 2017 and 2018 was found to be 56.55, 65.66 and 71.89 Kilotonnes respectively. Upon validation of calculated emission the discrepancy of 2.59% was found. The CO₂ emission was forecasted up-to 2030 considering two scenarios namely, time series analysis and regression analysis. Lastly, for the CO₂ reduction from GSE the scenario; Electrical GSE and Construction of Aerobridge was studied and from which it was found that the CO₂ will be reduced by 80% if implemented.